Les bains-douches en Limousin, une hygiène populaire au début du XXe siècle - Colette Aymard (In Situ)
The historic monuments service in the Limousin region has recently carried out an inventory of the region’s ‘bains-douches’, that is to say the public bathing and shower facilities. This regional corpus was an opportunity for carrying out some historical and architectural research on these popular bathing houses known as ‘bains de propreté’, or cleanliness baths. They were functional constructions, often of modest appearance and scale and they bear witness to evolving practices of hygiene in a social organisation that has now disappeared. The main providers of these bathing houses were local authorities, savings banks and low-cost housing associations.